Modeling Fischer–Tropsch kinetics and product distribution over a cobalt catalyst. Issue 7 (23rd February 2021) - Pandey, Umesh; Runningen, Anders; Gavrilović, Ljubiša; Jørgensen, Erik A.; Putta, Koteswara R.; Rout, Kumar R.; Rytter, Erling; Blekkan, Edd A.; Hillestad, Magne
Abstract: A detailed kinetic model describing the consumption of key components and product distribution in the Fischer–Tropsch synthesis (FTS) over a 20%Co/0.5Re γ‐Al2 O3 commercial catalyst is developed. The developed model incorporates the H2 O‐assisted CO dissociation mechanism developed by Rytter and Holmen and a novel approach to product distribution modeling. The model parameters are optimized against an experimental dataset comprising a range of process conditions: total pressure 2.0–2.2 MPa, temperature 210–230°C, CO conversion range of 10%–75% and feed with and without added water. The quality of the model fit measured in terms of mean absolute relative residuals (MARR) value is 23.1%, which is comparable to literature reported values. The developed model can accurately describe both positive and negative effects of water on the rate kinetics, the positive effect of water on the growth factor, temperature and syngas composition on the kinetics and product distribution over a wide range of process conditions, which is critical for the design and optimization of the Fisher–Tropsch reactors. Abstract : Catalyst deactivation as a function of the partial pressure of water in the feed.